The plurality of cultural references of food styles in African cities - (:unkn) unknown (My University, 2006)
The current debate about the effects of globalisation and market liberalisation frequently opposes global food to local food. This paper analyses food styles in urban Africa and shows that this dual approach must be replaced by a more complex vision, based on the plurality of cultural references in actors' behaviours. A first section presents the evolution of the approaches and methodologies used to characterise food styles. Namely, the type of food consumed is increasingly supplemented by the actors' practices and representations to explain food patterns. In our view, the plurality of references used by consumers can be explained by the fact that eaters belong to several communities at the same time and by cultural interbreeding.
Keywords: African Research